2008
DOI: 10.1029/2008ja013147
|View full text |Cite
|
Sign up to set email alerts
|

Persistent global proton aurora caused by high solar wind dynamic pressure

Abstract: [1] Global images of the proton aurora taken with the SI-12 camera onboard the IMAGE satellite reveal a very direct relationship between the solar wind dynamic pressure and the intensity of the global proton aurora. We show that an increase in dynamic pressure leads to an immediate and persistent increase in proton precipitation, also when the increase is slow. When the dynamic pressure decreases, the proton aurora diminishes. Five events during geomagnetic quiet times, with mostly northward IMF, have been sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…Thus, the loss cone of the protons can be expected to increase significantly and much more protons will get lost into the ionosphere. In addition to the pressure pulse mentioned here, the persisted solar wind pressure enhancement could cause the proton aurora, as have been reported in previous investigations (Laundal & Østgaard, ; Liou et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Thus, the loss cone of the protons can be expected to increase significantly and much more protons will get lost into the ionosphere. In addition to the pressure pulse mentioned here, the persisted solar wind pressure enhancement could cause the proton aurora, as have been reported in previous investigations (Laundal & Østgaard, ; Liou et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…We now know that high‐density plasma can amplify the damaging effects of magnetic storms [cf. Lyons , ; Zhou and Tsurutani , ; Liou et al ., ; Laundal and Østgaard , ; Weigel , ]. The highest solar wind densities in ICMEs are found in solar filament material [ Crooker et al ., ] and ICMEs are responsible for the most severe types of space weather [cf.…”
Section: Introductionmentioning
confidence: 99%
“…Zesta et al [2000] and Boudouridis et al [2003] found that the compression of the magnetosphere by an IP shock led to a global enhancement of the auroral-zone ionospheric currents and increase of the auroral emissions with poleward expansion of the auroral oval. It was also noticed that long-duration high solar wind ram pressure caused increase of the auroral intensity in the flanks of the auroral oval and there is a dawn-dusk asymmetry of the auroral luminosity [Liou et al, 2007;Laundal and Østgaard, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…The large-scale auroral transient signatures in response to the IP shock (i.e., shock aurora) were analyzed by several authors using satellite observations [e.g., Zhou and Tsurutani, 1999;Sibeck et al, 1999;Zhou et al, 2003;Laundal and Østgaard, 2008]. Shock aurora observed from satellites [e.g., Zhou and Tsurutani, 1999;Tsurutani et al, 2001] show that the aurora immediately brightens near local noon at the time of the shock arrival.…”
Section: Introductionmentioning
confidence: 99%